Are all “female-dominated occupations” poorly paid? - Hall, Anja [Verfasser]; Santiago Vela, Ana [Verfasser] (My University, 2021)
"Occupations with a very high proportion of women are designated as female-dominated occupations. Wages in female-dominated occupations are on average lower than in typical male-dominated occupations and in mixed occupations not dominated by women. Whether this average income-reducing effect of female-dominated occupations differs across educational levels and across occupational fields has not yet been analysed and forms the focus of the present article. Using the 2018 BIBB/BAuA Employment Survey, we first investigate whether the effect of female-dominated occupations is different for the group of employed persons with a vocational education and training (VET) degree than for the whole group of employed persons with all educational levels. Second, by focusing on employed persons with a VET degree, we analyse whether all female occupations are poorly paid or whether any differences arise depending on the specific field of the female-dominated occupation." (authors' abstract; BIBB-Doku)
Keywords: P 1.3 Frauen; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; 370; Frauenberuf; Geschlechtersegregation; Lohnhöhe; Einkommensunterschied; Qualifikationsniveau; Berufsbereiche; BIBB/BAuA-Erwerbstätigenbefragung